Особливості правового статусу керівника у структурі управління правоохоронними органами - Присяжнюк, О. А.; Prysiazhniuk, O. A. (Актуальні питання у сучасній науці. - 2024. - № 7(25). - С. 491-498, 2024)
Зазначено, що функціонування керівника в умовах сучасних викликів відзначається багатоплановістю та значним розшаруванням визначених законодавством його прав і обов’язків. Відзначено, що основними управлінськими формами реалізації своїх прав, обов’язків та повноважень керівником структурних підрозділів правоохоронних органів, вбачається формування та здійснення управлінських рішень, які уособлюються у виданні наказів, розпоряджень, доручень тощо, які є обов’язковими для виконання всіма без виключення підлеглими елементами організаційно – штатної побудови тих чи інших підрозділів правоохоронних органів, у тому числі конкретними особами, у випадках видання управлінських актів індивідуального характеру. Наголошено, що процес прийняття управлінського рішення керівником правоохоронного органу під час здійснення управління його структурними підрозділами, формується у складну систему, основні етапи якої становлять ініціювання та розробка проєктів управлінських рішень; прийняття управлінських рішень; перегляд управлінських рішень; виконання управлінських рішень; контроль виконання управлінських рішень тощо.

The manager plays an important role and has a direct influence on the formation of the level of work capacity and efficiency of the team of structural subdivisions of law enforcement agencies, the nature of the internal administration process, the style of relations between employees, a positive microclimate in the subdivision, etc. The leader is an entity that the legislation grants a wide range of powers, the right to make decisions from the position of sole leadership and hierarchical dominance, the determination of the legal status of the head of structural divisions of law enforcement agencies becomes especially important in the conditions of armed aggression of the Russian Federation and martial law. The article emphasizes that the functioning of the manager in the conditions of modern challenges is characterized by multi-planning and a significant layering of rights and duties defined by legislation. It was noted that the main administrative forms of the exercise of rights, duties and powers by the head of the structural subdivisions of law enforcement agencies are the formation and implementation of administrative decisions, which are embodied in the issuance of orders, orders, commissions, etc., which are mandatory for all subordinates without exception elements of the organizational and staff structure of certain units of law enforcement agencies, including specific persons, in cases of issuing administrative acts of an individual nature. It is emphasized that the process of making a management decision by the head of a law enforcement agency during the management of its structural subdivisions is formed into a complex system, the main stages of which are the initiation and development of management decision projects; management decisionmaking; review of management decisions; implementation of management decisions; control of the implementation of management decisions, etc.

Указано, что функционирование руководителя в условиях современных вызовов отличается многоплановостью и значительным расслоением определенных законодательством его прав и обязанностей. Отмечено, что основными управленческими формами реализации своих прав, обязанностей и полномочий руководителем структурных подразделений правоохранительных органов, усматривается формирование и осуществление управленческих решений, олицетворяющихся в издании приказов, распоряжений, поручений и т.п., обязательных для выполнения всеми без исключения подчиненными элементами организационно – штатного построения тех или иных подразделений правоохранительных органов, в том числе конкретными лицами, в случаях издания управленческих актов индивидуального характера. Подчеркнуто, что процесс принятия управленческого решения руководителем правоохранительного органа при осуществлении управления его структурными подразделениями формируется в сложную систему, основные этапы которой составляют инициирование и разработка проектов управленческих решений; принятие управленческих решений; пересмотр управленческих решений; выполнение управленческих решений; контроль выполнения управленческих решений и т.п.
Features of the legal status of the manager in the management structure of law enforcement bodies
Keywords: правоохоронний орган; керівник; правовий статус; адміністрування; управління; управлінське рішення; наказ; law enforcement agency; manager; legal status; administration; management; management decision; order; правоохранительный орган; руководитель; правовой статус; администрирование; управление; управленческое решение; приказ